Efeito anticárie do infiltrante resinoso incorporado com nanopartículas de hidroxiapatita no esmalte dental : estudo in situ - Segales, Sussan Daniela Salazar (2020)
The use of resinous infiltrant is a conservative option, however, its effect on the enamel adjacent to the infiltrated area exposed to oral biofilm formation, especially in intraoral conditions, has been little tested. The aim of this study was to evaluate the anticaries effect of resinous infiltrants containing amorphous or rod-shaped nanohydroxyapatite on the inhibition of enamel caries lesion adjacent to the infiltrated enamel. Secondly, the effect of infiltrants on the composition of the biofilm formed in situ was evaluated, as well as the effects of the cariogenic biofilm on the surface roughness of the infiltrants and of the incorporation of nanohydroxyapatites in the roughness of infiltrants were evaluated. This in situ study had two phases of 7 days each, and wash-out period with the same lasting. A total of 16 volunteers used palatal intraoral devices containing pH-cycling demineralized enamel slabs infiltrated with resinous infiltrate (IRbase); amorphous nanohydroxyapatite infiltrant (InHap0h) and rod-shaped nanohydroxyapatite infiltrant (InHap5h). Specimens of infiltrants and demineralized enamel were also placed in the intraoral devices. To simulate a clinical situation of high cariogenic challenge, the specimens were exposed to a 20% sucrose solution 8 times/day. The enamel demineralization adjacent to the infiltrated area was evaluated by enamel cross-sectional Knoop microhardness. The composition of the cariogenic biofilm was evaluated by counting the number of colony-forming units (CFU) of total microorganisms, total streptococci, S. mutans and lactobacilli. The effect of cariogenic biofilm on infiltrant´s roughness (Ra) was accessed by mechanical profilometry and scanning electron microscopy (SEM). After normality analysis, microbiological data were analyzed using Kruskal-Wallis and ANOVA tests, roughness and HKN data using ANOVA and Tukey tests, adopting 95% confidence. For CFU counts, no statistically significant differences were found (p> 0.05). The Ra of infiltrants increased significantly after the biofilm formation as well as with the incorporation of nanoparticles (InHap0h or InHap5h) (p> 0.05). However, Ra showed no statistically significant difference between InHap0h and InHap5h before or after exposure to cariogenic biofilm. The enamel hardness adjacent to the enamel infiltrated with InHap5h was significantly greater (p> 0.05) than the control enamel hardness up to 40-μm depth, at both 100 μm and 400 μm from the infiltrated area. It is concluded that the incorporation of nHAp5h in the resinous infiltrant can inhibit the caries lesion in adjacent enamel even in high caries risk situations, being a promising anti-caries material to control incipient caries.